KRIS-DQ Index: a structured tool for evaluating key risk disclosure quality among Malaysian public- listed companies - Osman, Amir Hakim; Abdullah, Azrul; Mahmud, Nurfarizan Mazhani (2025)
In the post-COVID-19 era, Malaysian public-listed companies face an increasingly complex risk landscape. Despite comprehensive regulatory frameworks, including the MCCG 2021, Bursa Malaysia Listing Requirements, and the Companies Act 2016, corporate risk disclosures remain limited, inconsistent, and focused on traditional financial and operational areas. This study introduces the Key Risk Disclosure Quality Index (KRIS-DQ Index), a scoring system developed to assess the quality of key risk disclosures in annual reports. Built on KPMG's post-pandemic key risk framework and aligned with national policies, the index covers 18 risk categories and evaluates each on a five-level scale, from non-disclosure to quantitative reporting. The KRIS-DQ Index was applied to 225 Main Board companies listed on Bursa Malaysia for the year 2023. The results show a wide range of disclosure quality, with a mean score of 51.3%, revealing gaps in strategic, ESG, and cybersecurity risk reporting. This study contributes to regulatory compliance, investor confidence, and academic research by offering a consistent and practical framework for benchmarking risk disclosure practices.